P307 Clinical profile of fusarium infections: case series from a tertiary care hospital. (20th September 2022) - Vineeth, VK; Sethuraman, Nandini; Gopalakrishnan, Ram
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Objective: To study the clinical profile of patients with Fusarium infections diagnosed at our tertiary care center during the study period from February 2017 to March 2022. Methods: We conducted a retrospective case study wherein all consecutive patients with Fusarium infections between February 2017 to March 2022 were accessed. The diagnosis was categorized based on either fungal culture alone or fungal culture with histopathology findings. Results: A total of 12 patients with Fusarium infections were encountered during this period. The mean age was 49. In all, 5 were females and 7 were males, and 5 patients had diabetes as a risk factor. Other risk factors included were chemotherapy for multiple myeloma (1) and lymphoma (1), polytrauma (1), and surgery after pituitary macroadenoma. A total of 8 (66.7%) patients were on antifungal prophylaxis at the time of diagnosis. A total of 6 (50%) had localized infections whereas, remainder 6 (50%) had disseminated infection, and 25% presented with onychomycosis. Seven patients were diagnosed based on fungal culture and five were diagnosed based on histopathology findings collaborated with a fungal culture. There was one patient with Fusarium blood stream infection, who expired within 2 weeks of hospitalization. A total of 10 patients had F. solani whereas, 2 had F. oxysporum isolated in fungal cultures. In all, 42% of patients in the study had high Beta- D-Glucan (BDG) and 67% of the patients underwent source control of the involved region. A total of 9 patients (75%) received voriconazole as antifungal treatment and 3 patients received Amphotericin B. Four patients expired, three were lost to follow up and five did not develop relapse on follow-up. Conclusion: Fusarium is an opportunistic human pathogen severely affecting immunocompromised patients, especially patients with hematological malignancies, prolonged neutropenia, and post-hematopoietic stem cell transplantation. Our study records a notable number of Fusarium infections among diabetics and onychomycosis was a common presentation. A high index of suspicion is of utmost importance in patients with risk factors and serum BDG may help in suspicion of invasive Fusarium infections. The 33% mortality in our study stresses the need for early diagnosis and treatment.